A Comparative Analysis of Nepal's Citizenship Law from the Perspective of Dual Citizenship (The Journal of Knowledge and Innovation, 2024)
This article presents a comparative study of Nepali citizenship law in relation to dual citizenship. Dual citizenship means that a person holds the citizenship of two countries simultaneously. The main purpose of this article is to determine whether the citizenship law of Nepal adopts a mono-citizenship policy or a dual-citizenship policy. The study examines Nepali citizenship law in the context of birth, marriage, residence, treaty, and default scenarios that may lead to dual citizenship. It includes a comparative analysis of the Nepali Citizenship Act (1952), Nepal Citizenship Act (1964), and Nepal Citizenship Act (2006). Additionally, examples of constitutions and citizenship laws from different countries are presented to support the arguments. The study finds that dual citizenship can arise from the aforementioned grounds, as well as from the reacquisition of citizenship, honorary citizenship, and non-resident citizenship.